Review: 'Morandi, Balla, de Chirico and Italian Painting 1920–1950', Tornabuoni Art Gallery, London, 12 February – 18 April 2020. Catalogue: Tornabuoni Art Gallery, London, 2020, 176 pages, hardback, £20, 00. (2020) - Traversaro, Chiara
No abstract available